2019
DOI: 10.1021/acs.jpca.9b08601
|View full text |Cite
|
Sign up to set email alerts
|

Protein Translational Diffusion and Intermolecular Interactions of Globular and Intrinsically Unstructured Proteins

Abstract: The study of intermolecular interactions of proteins has been an important problem for many years. This paper presents an approach to analyze different levels of protein interactions in solutions through a set of the secondand higher-order virial coefficients. The proposed approach is based on the diversified analysis of protein translational collective diffusion and self-diffusion obtained by dynamic light scattering and the pulsed-field gradient NMR (PFG NMR) spectroscopy experimental data. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…This theory has also been used to study bovine serum interaction to different solid surfaces 33 . This theory has also been modified to study protein–protein interaction 34,35 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory has also been used to study bovine serum interaction to different solid surfaces 33 . This theory has also been modified to study protein–protein interaction 34,35 …”
Section: Introductionmentioning
confidence: 99%
“…33 This theory has also been modified to study protein-protein interaction. 34,35 All these studies suggest that the surface energetics approach, utilizing XDLVO theory, has the potential to understand protein interaction to ion exchange chromatographic supports, which has never been attempted earlier. Hence, this study is an attempt to find out the interaction behavior of proteins to ion exchange chromatographic material by XDLVO theory/surface energetics approach.…”
Section: Introductionmentioning
confidence: 99%
“…To realize the knob-hole contacts, the fibrin molecules have to approach each other to make possible a more or less parallel orientation (Figure 2) defined by the weak nonspecific interactions such as the electrostatic repulsion and the van der Waals attraction. 18,25 In the case of the elongated asymmetric Fg molecules, these interactions are "amplified" due to the nonspherical asymmetry of charge distribution and interactions between point electric charges and their dipoles. 18,26,27 An important role of weak interactions is to control a relatively long-ranged attraction−repulsion balance leading to a parallel orientation of the Fg molecules and further fibrin polymerization 28 (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Early, we have shown that the shape of concentration dependence for the protein collective diffusion manifests a current balance between different weak interprotein interactions. 25,39,44,45 The experimental data on the protein collective diffusion as a function of the volume fraction φ is possible to present with a set of virial coefficients 46…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation